Utilization and Acceptability of Telemedicine during COVID-19 Pandemic for the Diabetes Care as an Alternative to Physical Examination (Medical Forum Monthly, 2023)
Objective: To know the utilization and acceptability of telemedicine during COVID -19 pandemic for the diabetes care as alternative to physical examination.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Services Hospital Lahore from 1st December 2020 to 31st May 2021.Materials and Methods: This cross-sectional study was conducted at the Services Hospital Lahore after approval of institutional review board (Ref No.IRB/2020/702/SIMS dated 19-09-2020). Total of 493 patients who had meet the inclusion criteria were interviewed with a questionnaire in Urdu language. Questionnaire was based to know the acceptability in terms of issue resolution, privacy concerns, cost effectiveness, time saving and problems faced while using telemedicine and their overall satisfaction.Results: Of 493 patients included in this study, mean age was noted to be 45.9±12.9 years and majority (55.6%) were male. Phone call mode was the most used method by 59.6% of patients for telecommunication as compared to Whatsapp (40.4%). Regarding education level, 83.5% have education level below matric. Majority of people (83.2 %) belongs to rural area. Level of education and residence has significant impact on choice of telemedicine modality (p value < 0.005). Willingness to use telemedicine in future was shown by 96.34% of participants.Conclusion: It was concluded that most of the patients were satisfied with the services and want to continue using telemedicine. The main problems faced were time limitation and busy number. To minimize these problems there should be a dedicated team for running this telemedicine at least 12 hours per day.